Enhancing Elementary School Students' Soft Skills Through the Parent Teaching Program: Leveraging Local Resources for Optimization - Irawan, M. Ferry; Noptario, Noptario; Abdullah, Faisal; Imtihana, Aida; Nurlaila, Nurlaila; Putri, Nadya Syafira (Journal of Integrated Elementary Education, 2024)
This study employed an explanatory sequential design to investigate the implementation of the parent teaching program and its impact at an elementary school in Yogyakarta, Indonesia. It was conducted in two stages: distributing and analyzing questionnaires to 76 students in the first stage and interviewing teachers and parents in the second stage. Data analysis employed basic statistics for quantitative analysis and thematic analysis for qualitative aspects. The results indicate that the parent teaching program at this school commences with the program's planning stage, during which teachers directly involve parents in meetings. The program is implemented after final exams or a week before the school holidays. It has a positive impact on the development of students' soft skills. Following the program's implementation, students demonstrated increased teamwork, communication, and creativity activities. Additionally, the program boosted students' self-confidence and critical thinking skills, which could benefit them in the future. It can be concluded that this program represents an innovative approach to enhancing students' soft skills by making use of local resources.